Geochemistry and degree of organic carbon preservation in non-bioturbated, shaly sediments - István Vetó; Magdolna Hetényi; Attila Demény; Ede Hertelendi (PANGAEA, 1994)
Based on 13 published porewater H2S and sulphate profiles the amount of H2S escaping from non-bioturbated shales varies between some few % to 45% of the amount of bacterially generated H2S. This finding permits calculation of the original organic carbon (TOCor) content of immature nonbioturbated shales using TOC and sulphur content data. In two immature non-bioturbated sequences from Hungary (Toarcian and Oligocene) the first-order correlation between HI and TOC/TOCor was found to be stronger than that between HI and TOC, indicating that sulphate reduction was the leading process both in decrease in TOC content and degradation of kerogen source potential.
Supplement to: Vetó, I et al. (1994): Hydrogen index as reflecting intensity of suiphidic diagenesis in non-bioturbated, shaly sediments. Organic Geochemistry, 22(2), 299-310, https://doi.org/10.1016/0146-6380(94)90176-7